P–501 Deep in the Maze: The psychosocial trajectory and decision making of Women with recurrent implantation failure of IVF. (6th August 2021) - Guo, D; Du, L; Chan, C H Y
Abstract: Study question: To understand the psychosocial trajectory of Chinese women who have experienced recurrent implantation failure (RIF) of IVF and their decision making accordingly. Summary answer: Chinese women experience despair, doubt, and disorientation along with the cumulative failure cycles of IVF, and stick to IVF as the ultimate option. What is known already: Recurrent implantation failure, the absence of implantation after repeated embryo transfers is a stressful event for people undergoing treatment for infertility. Numerous researches have focused on the psychological wellness of women undertaking IVF, but pay less attention to the subgroup who have undergone repeated failures. Current studies have shown that women after repeated unsuccessful IVF might endure anxiety, depression, and other psychosocial distress; however, the feelings brought by the different times of failure are unlike, and these experiences will affect their treatment decisions accordingly, which is rarely studied. Study design, size, duration: Semi-structured interview was adopted with sixteen Chinese women from March 2020 to July 2020. The interview lasted 90 minutes. A follow-up survey was conducted three months after the interview. Driven by grounded theory, data is analyzed by thematic analysis. Participants/materials, setting, methods: Convenience sampling was used to recruit female participants who have failed to achieve clinical pregnancy after two consecutive cycles of fresh or frozen IVF embryo transfers with a cumulative number of transferred embryos of four or more cleavage-stage embryos or two or more blastocysts. Chinese-speaking women who were undertaking IVF treatment in the reproductive center of hospital in Shenzhen City were recruited by pamphlets and doctors' referral. Main results and the role of chance: Chinese women with recurrent implantation failures experience the following psychosocial trajectory during the cumulative failure cycles of IVF: despair, doubt, and disorientation. Despair usually comes after the first failure: the high expectation for success rates makes the initial failure exceptionally shocking and desperate. Huge distress brings two kinds of decisions: start a new IVF cycle quickly to welcome the positive results in the imagination, or wait for a period of time to avoid the pain of failure again. Doubt usually appears after the second failure. In addition to doubting the health function of their body, recurrent failure makes the patients particularly doubt the efficacy of IVF and doctors' clinical judgment. Some patients would do 'hospital shopping' and consider change clinics. Disorientation can be seen in patients who have experienced more than three cycles of failure. Past experience and meaning cannot help them understand and solve the current dilemma. The inherent concept of fertility continues to strengthen their belief of having a baby as ultimate goal. The follow-up survey found that most women still choose to continue IVF treatment after repeated failure. They are like being in the maze of fertility, wandering for a long time but unable to get out. Limitations, reasons for caution: Several limitations are identified: self-selection bias due to convenience sampling; narrow sampling approach may limits the generalizability; the exclusion of men may ignore the marital interdependence during the infertility treatment. Wider implications of the findings: Patients who have experienced recurrent implantation failure demand promising intervention during and after infertility treatment. The findings demonstrate the need for both supportive and implication counseling to facilitate them cope with the psychosocial distress, and make value-based decision making, so as to enhance their self-agency. Trial registration number: Not applicable